Implementasi Kegiatan Keagamaan dalam Menanamkan Karakter Religius Masyarakat di Desa Kesaud Kota Serang - Asiah Asiah; Dhana Risya Aulia; Juedi Juedi; Muhammad Nuriya Arsy Hannan; Nanda Ibrahim; Sari Natasya; Sobriyah Sobriyah; Silfia Silfia (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This article discusses the implementation of religious activities in instilling religious character in Kesaud Village, Serang City. Religious character consists of attitudes, motivations, and skills that are influenced by religious values and teachings. Through activities such as recitation, congregational prayers, and reading dalail khoirat, the community is invited to increase faith and form behaviors that reflect religious teachings. However, there are several obstacles in the implementation of these activities, such as the lack of educators and budget limitations. This has resulted in a decline in community participation in religious activities. To overcome these challenges, changes in the management of the organization and the mindset of the community are needed. This article also highlights the importance of youth organizations, such as RISMA, in attracting people to participate in religious activities. Thus, it is hoped that religious characters can be well embedded in the daily lives of the people of Kesaud Village.